Applying the One Health Approach to Rabies Control in the Timor Archipelago, East Nusa Tenggara: A Literature Review on Epidemiology and Strategic Interventions - Kale, Maria Laurenci Fanny Permata; Riwu, Audrey Gracelia; Simarmata, Yohanes TRMR; Wuhan, Yustinus Oswin Primajuni; Loe, Fhady Rischky (Cendana Medical Journal, 2025)
Background: Rabies remains a fatal zoonotic threat in Indonesia, particularly in East Nusa Tenggara (NTT), including Timor Island. Despite national efforts, the disease persists with rising incidence, especially in areas with high dog populations, limited vaccination coverage, and weak cross-sectoral coordination. Objective: This review aims to assess the recent epidemiological trends of rabies in Timor Island and evaluate the effectiveness of One Health implementation in controlling the outbreak. Methods: A literature review was conducted using data from 2010–2025 from sources such as WHO, FAO, Indonesian government agencies, and peer-reviewed journals. Keywords included “rabies,” “One health,” “NTT,” “Timor,” and “epidemiology.” Data were analyzed descriptively and thematically to identify gaps, risks, and strategic responses. Results: Rabies remains endemic in Timor, with more than 50,000 dog bite cases and over 80 human deaths recorded between 2023–2024. Vaccination coverage in dogs remains as low as 17.6%, and there are only 324 vaccinators for the entire province. Social and cultural factors, such as free-roaming dogs and limited public awareness, contribute significantly to transmission. Implementation of One Health remains fragmented, with low community involvement and weak surveillance integration across sectors. Conclusion: A locally adapted One health approach is urgently needed to eliminate rabies in Timor. Strengthening dog vaccination, integrating digital case reporting, engaging traditional leaders, and enforcing village-based regulations are key to effective rabies control. Keywords: Rabies, Timor Island, One health, Dog Vaccination, Community Engagement, Indonesia